Evaluation of Dry Eye After Refractive Surgery According to Preoperative Meibomian Gland Status - Gong, Qianwen; Li, Anqi; Chen, Lin; Chen, Huijuan; Gu, Jinjing; Xu, Zhiqiang; Lu, Fan; Hu, Liang (Frontiers in Medicine, 2022)
Purpose To investigate the effect of the preoperative meibomian gland (MG) status on dry eye symptoms after corneal refractive surgery. Methods This is a prospective, observational study. Subjects were enrolled and classified into 3 groups according to their MG loss grades. Ocular surface parameters were measured preoperatively and at 1, 3, and 6 months, postoperatively, including the ocular surface disease index questionnaire (OSDI), non-invasive tear film break up time (NIBUT), tear meniscus height and Schirmer I test. All the parameters were analyzed among the three groups, and different time points. Results Seventy-eight patients were included in this study. The grade of MG loss varied from 0 to 2, thus the subjects were divided into group 1–3 corresponding to the MG loss. There were no significant differences in all parameters at baseline. The OSDI score increased in all groups at 1 month postoperatively and then decreased after other follow-ups. The OSDI was higher in group 3 than group 1 at all time points postoperatively (P = 0.005, 0.002, 0.034). Besides, it was higher in group 2 at 3 months and 6 months, compared with group 1 (P = 0.006, 0.029). The average NIBUT was shorter in group 3, compared with group 1 and group 2 since 1 month after surgery. At 1 and 3 month postoperatively, the grade of MG loss was positively correlated with the total OSDI and the vision-related scores. And it showed a positive correlation only with the environmental score at 6 months postoperatively. Conclusions The dry eye discomfortable symptoms significantly differed post operatively according to their preoperative MG loss grade, though no difference was found at baseline. Dry eye was associated more with vision-related discomfort at first and environmental factors later.